Language Use in TikTok Activism by Gen Z Communities - Cika Aprilia (Pemuda Peduli Publikasi Insan Ilmiah, 2025)
Purpose: This study investigates the linguistic behaviors of Generation Z in TikTok-driven protest movements and explores their implications for management studies. It examines how Gen Z employs creative language practices to construct activist discourse and challenge institutional authority within global digital platforms. Subjects and Methods: Employing a qualitative approach, the study analyzes linguistic tools such as satire, vernacular codes, emotional appeals, and participatory memes within TikTok content created by Gen Z communities. Data were drawn from online observations and discourse analysis of protest-related materials, focusing on how these practices shape communicative dynamics. Results: The findings indicate that Gen Z’s targeted linguistic actions on TikTok represent a sophisticated form of discursive agency. Rather than being ephemeral, these practices influence the image of social groups, corporate reputation, and stakeholder legitimacy. Within management contexts, Gen Z activism disrupts traditional organizational communication, creating new challenges for stakeholder engagement and crisis management. Activists function as decentralized communication agents, compelling institutional actors to respond to digitally constructed meanings. Conclusions: The study concludes that organizations must adapt to communication environments characterized by linguistic hybridity, digital remix culture, and affective connectivity. Managers are urged to recognize and engage with these dynamics proactively to maintain ethical authenticity and value alignment.